(Table 1, pages 121-126) Major and minor element composition of sedimentary core samples from DOMES Site C, Pacific Ocean - James L Bischoff; David Z Piper (PANGAEA, 1976)
The study of the chemical composition of DOMES Site C sediment was undertaken in order to establish important baseline parameters in the overall characterization of the sediment. Such general characterization and information concerning heterogeneity and local variation of this and related parameters such as mineralogy, sediment age, and pore water chemistry, are essential in formulating predictive models concerning environmental perturbations caused by resuspension of sediments during deep sea mining.
Supplement to: Bischoff, JL; Piper, DZ (1976): Chemical composition of marine sediments of DOMES Site C. in: Deep Ocean Mining Environmental Study, N.E. Pacific Nodule Province, Site C, Geology and Geochemistry, U.S. Geological Survey Open File Report. U.S. Geological Survey, 113-130, https://store.pangaea.de/Projects/NOAA-MMS/bischoff2_DomesC_Analyses.pdf